Al-Jarh wa Ta'dil Method Buku Siyar A'lam an-Nubala by Az-Dzahabi Case Study of Ibn Darastaweh - Syamsudin; Dadah; Muhammad Al Mighwar; Engkos Kosasih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The aim of this research is to explore the methodology of writing the book Siyar A'alam an-Nubala by al-Hafidzh Az-Dzahabi as a practice of rijal science, both Tarikh ruwat and Jarh wa Ta'dil. Because with these two disciplines we can trace the credibility of a rijal (narrator) and find out about the history of the narrator. One of the writing methods in Tarikh Ruwat is the thabaqat style. And in this case, we will present the book Siyar A'alam an-Nubala to examine its writing method so that the author hopes that scholars, especially activists in the field of hadith, can find out the description of the book and the technicalities of its use. This writing uses the library research method, with a qualitative approach. And the author also presents sample cases discussed in the book as practice for analyzing the results of this research.